The Megalithic Site of Pekauman Village: Distribution Patterns, Historical Studies, Forms, and Functions in the 6th-16th Centuries - Muhammad Fadlal Khairy Ibrahim (Journal of Indonesian History, 2025)
Research on the Megalithic Site of Pekauman Village in Bondowoso was motivated by the lack of a definitive chronology regarding the development of megalithic traditions in the region, despite the abundance and diversity of its relics. The range of findings indicating the continuity of the tradition from the 6th to the 16th century AD raises important questions about cultural continuity, changes in the function of artifacts, and the relationship between the communities that supported this tradition and regional historical dynamics, including the influence of Hinduism, Buddhism, and Islam. Previous studies have focused more on the inventory of artifacts, so research is needed that is capable of reconstructing the distribution patterns, developmental forms, and functions of the remains in a more comprehensive manner. The method used is a historical research method that includes heuristics, source criticism, interpretation, and historiography. This process involves the collection of archaeological data, historical documents, and spatial context analysis to interpret changes in the function of artifacts such as sarcophagi, dolmens, kenong stones, menhirs, and terraced punden. This approach allows for the reconstruction of the development of the megalithic tradition through three major phases: the early phase (6th–8th centuries), the middle phase (9th–13th centuries), and the final phase (14th–16th centuries AD), each of which shows social and religious transformations as well as the spatial arrangement of the supporting communities. The results of the study show that the megalithic remains in Pekauman have a tendency to cluster near water sources and residential areas, and serve a dual function—both as a means of ancestor worship and as a social and agrarian marker. This analysis also confirms the continuity of the megalithic tradition, which has survived through various cultural periods, despite a decline in artifact production in the final phase. In addition, the relocation of some artifacts to the Megalithic Information Center (PIM) further strengthens our understanding of the historical distribution density of this site. In conclusion, this study provides a clearer chronological and functional picture of the development of the megalithic tradition in Pekauman, while also confirming the village's position as one of the important centers of megalithic culture in East Java. These findings not only enrich regional archaeological understanding, but also provide an important basis for the preservation and further study of prehistoric cultural continuity.